2001
DOI: 10.4049/jimmunol.166.4.2627
|View full text |Cite
|
Sign up to set email alerts
|

Fes Mediates the IL-4 Activation of Insulin Receptor Substrate-2 and Cellular Proliferation

Abstract: Although Jak kinases are essential for initiating cytokine signaling, the role of other nonreceptor tyrosine kinases in this process remains unclear. We have examined the role of Fes in IL-4 signaling. Examination of Jak1-deficient cell lines demonstrates that Jak1 is required for the activation of Fes by IL-4. Experiments studying signaling molecules activated by IL-4 receptor suggest that IL-4 signaling can be subdivided into Fes-dependent and Fes-independent pathways. Overexpression of kinase-inactive Fes b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 69 publications
0
19
0
Order By: Relevance
“…Tyrosine phosphorylation of Bcr on Tyr-177 and Tyr-246 by Fes suppresses Bcr serine/threonone kinase activity toward 14-3-3 protein BAP-1 , but induces association with Grb2/mSOS, the Ras guanine nucleotide exchange factor complex (Maru et al, 1995). Signaling downstream of the IL4Ra involves Fes-mediated PI3K recruitment and activation of p70 S6K but not Akt kinase (Jiang et al, 2001). Ras activity as well as activation of the Rho family of small G proteins Rac and Cdc42 are required for ®broblast transformation of myristylated c-Fes (Li and Smithgall, 1998).…”
Section: C-fes/fpsmentioning
confidence: 99%
See 2 more Smart Citations
“…Tyrosine phosphorylation of Bcr on Tyr-177 and Tyr-246 by Fes suppresses Bcr serine/threonone kinase activity toward 14-3-3 protein BAP-1 , but induces association with Grb2/mSOS, the Ras guanine nucleotide exchange factor complex (Maru et al, 1995). Signaling downstream of the IL4Ra involves Fes-mediated PI3K recruitment and activation of p70 S6K but not Akt kinase (Jiang et al, 2001). Ras activity as well as activation of the Rho family of small G proteins Rac and Cdc42 are required for ®broblast transformation of myristylated c-Fes (Li and Smithgall, 1998).…”
Section: C-fes/fpsmentioning
confidence: 99%
“…The gp130 signal-transducing subunit forms a part of the IL-6-related cytokine subfamily receptors, and is associated with Fes in the absence of receptor stimulation, while Fes becomes tyrosine phosphorylated after IL-6 stimulation (Matsuda et al, 1995). Fes interacts also with the IL-4Ra subunit and becomes tyrosine phosphorylated by JAK1 upon ligand binding (Izuhara et al, 1994;Jiang et al, 2001). The involvement of Fes in mediating signals downstream of the common b (b c ) subunit, which is part of the IL-3/IL-5/GM-CSF receptor complex, and the erythropoietin (EPO) receptor are however more controversial.…”
Section: C-fes/fpsmentioning
confidence: 99%
See 1 more Smart Citation
“…[17][18][19][20]47 In primary erythroid cells, the activation of FES and/or FER downstream of wild-type KIT receptor has been suggested using a dual-specific antibody. 25 Another study showed increased FER phosphorylation in response to SCF in BMMCs.…”
Section: Fes Fer and Cell-surface Receptorsmentioning
confidence: 99%
“…FES (feline sarcoma) and FER (FES-related) proteins are the only 2 members of a subfamily of cytoplasmic protein tyrosine kinase. 16 FES has been shown to associate with growth factor and cytokine receptors, [17][18][19][20] which leads to activation of its catalytic activity through tyrosine phosphorylation. The downstream effectors of FES are not clearly characterized, although several studies point to a link between FES and several signaling proteins such as STATs, [21][22][23] the MAP kinases ERK-1 and ERK-2, 24,25 and PI3K.…”
Section: Introductionmentioning
confidence: 99%